(untitled) (World Economics and Finance Bulletin, 2022)
It is known from the world experience that privatization of state enterprises has a significant positive effect on economic development. At the moment, Japan (5 percent) has the highest state ownership of enterprises in the world. This indicator is 11 percent in other developed countries, in particular, in the USA, 18 percent in Germany, and 22 percent in South Korea. In Uzbekistan, 55 percent of the enterprises are owned by the state